Effect of arbuscular mycorrhiza on germination and initial growth of Cinchona officinalis L. (Rubiaceae). - Fernandez-Zarate, F. (2022)
Cinchona officinalis, known locally as cascarilla or cinchona, is a plant species native to South America. It was used as a source of quinine to combat malaria in the 17th century. The species is threatened by various anthropogenic activities. Further, the propagation of the species depends on seed dispersal and its germination capacity. Therefore, it is necessary to conserve and propagate this species. Because C. officinalis seeds have a low germination capacity, we determined the effect of arbuscular mycorrhizae (AM) on their germination and growth. A randomized design was employed with two treatments, one treated with mycorrhizae (CM) and another without mycorrhizae (SM). For each treatment, three replicates of 100 seeds were used. Germination, growth, and fungal characteristics were evaluated. In germination parameters, the CM treatment showed better performance, but the improvement was statistically insignificant. However, the application of AM significantly improved seedling height (cm), root length (cm), leaf area (cm2), and root number by 53.52, 28.72, 29.73, and 61.66%, respectively. Likewise, mycorrhization intensity (%), mycorrhization frequency (%), and extraradical mycelium length (cm) in the CM treatment were 37.13, 3.44, and 174.97% higher compared to the SM treatment, respectively. Therefore, the use of AM fungi proves to be advantageous in the propagation of C. officinalis, and these results provide a basis for the largescale and sustainable propagation of this species.